A study on influence of superparamagnetic iron oxide nanoparticles (SPIONs) on green gram (Vigna radiata L.) and earthworm (Eudrilus eugeniae L.) - Samrot, Anthony V.; C., SaiPriya; A., Jenifer Selvarani; R., Venket Subbu; P. J., Jane Cypriyana; Y., Lavanya; R., Shehanaz Afreen; P., Soundarya; R. B., Sherly Priyanka; P., Sangeetha; Varghese, Reji Joseph; S., Suresh Kumar (IOP Publishing, 2020)
Nanoparticles usage are now emerging as hazardous nanopollutants due to inappropriate usage and improper disposal. Superparamagnetic Iron Oxide Nanoparticles(SPIONs)is a widely used nanoparticle with various applications. In this study, SPIONs was evaluated for its impact against Vigna radiata and Eudrilus eugeniae. SPIONs were synthesized by chemical co-precipitation method in presence of cobalt chloride. The produced SPIONs was characterized using UV-Visible Spectroscopy, SEM (Scanning electron microscopy), EDX (Energy dispersive X-ray spectroscopy), XRD (X-ray diffraction), TEM (Transmission electron microscopy), AFM (Atomic force microscopy), XPS (X-ray photoelectron spectroscopy) and Zeta potential. The synthesized SPIONs were crystalline and monodispersed with size ranging between 15 nm and 20 nm. The seedlings of SPIONs treated Vigna radiatawere found to have reduced root and shoot growth. The bioaccumulation of iron oxide in the treated plants was confirmed by ICP-OES (Inductively coupled plasma - optical emission spectrometry) analysis and Prussian blue staining. Cellular destruction and reduced reproduction rate were found in SPIONs exposed Eudrilus eugeniae and ICP-OES analysis of earthworm samples affirmed the bioaccumulation of SPIONs.